Gospodarstwo rodzinne jako podstawa europejskiego modelu rolnictwa - Tańska-Hus, Bożena (Family Farm as a Basis of the European Agriculture Model, 2006)
The paper attempts to find a legal and uniform, for the whole EU area, definition of the agricultural farm and family farm in the primary community law, that would enable to define in detail its tasks and functions and would also define its legal status and, therefore, would define it as a subject of some defined rights and duties.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 438-442